Applicability of Solid Lubricant Coatings in Cold Rod Extrusion of Stainless Steels - Jobst, Andreas; Merklein, Marion (Defect and Diffusion Forum, 2020)
Cold extrusion is an established technology for the production of dimensionally accurate components in large series. Due to the high material and energy efficiency, a resource-saving manufacturing of high-performance parts is possible. Forming at room temperature leads to an advantageous grain structure and work hardening of the material, resulting in components with favorable operating characteristics. Nevertheless, a challenge is the generation of residual stresses during forming, which are influencing the fatigue behavior. The modification of the tribological conditions is one method for influencing the parts’ residual stress state. However, the high strength and work hardening of the materials formed at room temperature leads to high tribological loads between billet and die. These challenges are intensified by the increasing use of stainless steels due to growing demands for corrosion resistant components. The aim followed within this paper is therefore to investigate the applicability of typical lubricant coatings in the forward rod extrusion of stainless steels. For this purpose, the ferritic stainless steel X6Cr17 (DIN 1.4016) and the ferritic-austenitic stainless steel X2CrNiMoN22-5-3 (DIN 1.4462) are extruded with an equivalent plastic strain of ε̅ ≈ 1. The research is performed with a molybdenum disulfide (MoS2), a soap and a polymer-based lubricant coating. For reproducing different contact conditions, the die geometry is varied with die opening angles of 60°, 90° and 120°. The suitability of the lubricants is evaluated using the integrity of the lubricant coating after forming. From the correlations between process forces, temperatures and surface integrity, recommendations for the application of the researched lubricants are derived.